Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPS dengan Model Cooperative Learning Tipe Picture and Picture di Kelas V SD - Marlina, Rosi; S, Farida; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe purpose of this study was to describe the improvement of student learning outcomes in social studies learning using the Coperative learning Model Picture and Picture at grade five B of SDN 06 Padang Besi, Padang City. The subjects of this study were teacher (practitioners) and 22 students. The type of this research used was Classroom Action Research using qualitative and quantitative approaches. The research was conducted in two cycles with research procedures consisting of planning, implementing, observing, and reflecting. The results showed an increase in aspects of: a) RPP, the average cycle I obtained was 80.3% increased to 96.4% in cycle II, b) aspects of the teacher and aspects of students, in the average cycle I obtained 77.7% increased to 94.4% in cycle II, and c) student learning outcomes in the average cycle I obtained were 76.4, in cycle II it increased to 90.7.Keywords : IPS, Cooperative learning Type Picture and Picture